Dispersive transport in porous media with biofilms: local mass equilibrium in simple unit cells. (6th December 2010) - Wood, B.D.; Golfier, F.; Quintard, M.
In this work, we continue our study of upscaling biofilm processes in porous media from the pore scale to the Darcy scale. We adopt a continuum-level description of biofilms at the pore scale on the basis of work reported in Wood et al. (2002b). We upscale from the pore scale to the Darcy scale using the method of volume averaging and we predict the effective dispersion tensor with two- and three-dimensional closure problems. Our results indicate that, for a one-equation local mass equilibrium theory, the primary influence of the biofilm is that the effective diffusion coefficient is smaller than it would be without the presence of biofilm. This effect is important primarily at low Peclet numbers.